GAYA KOMUNIKASI MUBALIGH DALAM SOROTAN PUBLIK - YERA YULISTA (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2016)
When preaching preachers will use a variety of communication styles.Communication style is a set of behaviors that can be used communicator(preachers) in conveying the message to get a certain response in certainsituations anyway. Style of communication in the form of verbal and nonverballanguage may be spontaneous or its use should be regulated in such a way thatthe purpose of the communication itself can be achieved. The figure of thepreacher as a public figure is implicitly demanded by the public can provideexemplary through their behavior, then what would happen if at some timepreachers bring communication styles that are considered unfit